Biodiversity in playa wetlands in relation to watershed disturbance - Malone, Willow Elaine Anna (Kansas State University, 2016)
Playa wetlands are unique ecological systems crucial to the ecology of the western Great Plains of North America. Playas offer a variety of ecological goods and services: flood water retention; water quality improvement; habitat for a distinctive assemblage of resident and migratory biota; and primary recharge points for the Ogallala Aquifer. The major threat to the function of playas is caused by watershed disturbance and habitat loss, primarily through sediment accumulation that decreases playa hydroperiod, density, and size. Previous research focused on playas in the Southern High Plains in Texas and the Rainwater Basin of Nebraska, with little playa studies located in the Central Great Plains. My objectives were to (1) identify the number and level of functionality of existing playas in the Smoky Hill River watershed, (2) determine the relative contribution of playas to the biodiversity of the landscape and influences from watershed disturbance levels, and (3) assess relationships among avian community composition and environmental variables through a canonical correlation analysis (CCA). To assess playa functionality, I randomly selected 20% of the 3,310 historical playas in the watershed and confirmed playa presence and anthropogenic modifications through imagery analysis (n = 608). To achieve the last two objectives, I conducted breeding bird surveys using point counts in >25 playas with paired, nonplaya sites. I recorded avian relative abundance and species richness. Plant species occurrence was detected using step-point methods along transects. Species diversity was derived using Simpson’s index. Approximately 22% of playas have been lost from the landscape. Of the remaining playas, only 3.15% were not affected by anthropogenic influences. Playas contribute greater than 40% and 16% greater avian species richness and diversity to the surrounding landscape, respectively. Playas located in grassland watersheds had a 63% and 35% greater avian species richness and diversity, as well as 57% and 66% greater floral species richness and diversity than playas located in croplands, respectively. CCA results identify playa soil moisture and watershed disturbance as significant influences to the playa avian community. It is important to reduce watershed disturbance and anthropogenic influence on playas to maintain biodiversity at local, regional, and continental scales.
Keywords: playa; diversity; watershed; disturbance; avian; flora